Partisipasi Politik Masyarakat Dalam Pemilihan Kepala Daerah Serentak Tahun 2024 di Desa Punggul Kecamatan Abiansemal Kabupaten Badung - I Made Wardana (STISIP Margarana, 2026)
This research examines political participation of Punggul Village community in the 2024 simultaneous regional head elections in Abiansemal District, Badung Regency. Using qualitative descriptive methods with 12 informants, the study found that political participation was classified as passive, with only 87.83% voter turnout, while youth participation (ages 17-30) was notably lower at 21.3%. Key findings indicate that political participation occurred primarily in three phases: before election (limited involvement in campaigns and political discussions), during election (voter turnout), and after election (acceptance of results). Driving factors included political stimulation reception, personal characteristics, social characteristics, and conducive political environment. Meanwhile, inhibiting factors consisted of residence outside the village, work and study commitments, low government trust, insufficient political education, household responsibilities, feelings of inadequacy, limited political socialization, and weaknesses in voter list compilation. The study concludes that community political participation remains largely passive, though some citizens demonstrated active participation through compliance with government decisions and acceptance of election outcomes.